Lived Experiences of Teachers in Challenging Areas in the Implementation of MATATAG Curriculum - Bensurto, Carren Delfin; Bernardino, Lebni Tenerife (Future Science / FSH-PH Publications, 2025)
This qualitative phenomenological study explored the lived experiences of teachers in challenging areas regarding the implementation of the MATATAG Curriculum. Fourteen purposively selected teachers from various schools in a district in Capiz participated in the study. Data were analyzed using coding and thematic analysis. Findings revealed that teachers viewed their role in implementing the MATATAG Curriculum as facilitators of holistic learning, adaptive instruction, and inclusive education. While most had attended seminars and workshops, they expressed a need for more specialized and in-depth training. Key challenges included a lack of instructional materials, time constraints, and difficulties in adapting to the new framework. The physical environment significantly impacted curriculum implementation, with inadequate classroom space and resources hindering effective instruction. Environmental barriers such as overcrowded classrooms and insufficient facilities further complicated execution. Teachers identified the need for additional support, including increased funding, more teaching resources, and enhanced professional development. They also emphasized the importance of administrative and community support in ensuring successful curriculum implementation. The MATATAG Curriculum showed promise in improving pupils’ academic performance and learning outcomes, but its effectiveness depended on sufficient instructional support and resources. To overcome implementation challenges, teachers recommended stronger stakeholder collaboration, curriculum refinements, and enhanced training programs. They also highlighted the importance of adopting innovative and adaptive teaching strategies.These findings suggest that the successful implementation of the MATATAG Curriculum requires a comprehensive approach that integrates teacher training, resource allocation, and institutional support. Addressing the identified challenges and barriers will strengthen curriculum delivery and enhance student learning outcomes.